The Influence of Population Aging on Living Carbon Emissions in the Yellow River Basin: Comparisons Between Urban and Rural Areas - Mei Song; Jia Zhang; Mengxue Li; Yujin Gao (Energy Science & Engineering)
ABSTRACT Population aging presents a major challenge to China's economic and social development. While some research has addressed the relationship between population aging and energy consumption or generalized carbon emissions, its impact on living carbon emissions has been less explored. This study uses provincial panel data from the Yellow River Basin (2006–2020) and employs a threshold regression model to analyze the relationship between population aging and living carbon emissions. A Multiple Mediation Effect Model is also applied to explore the mechanisms behind this relationship, with a comparative analysis between urban and rural areas. The results indicate a U‐shaped nonlinear effect of population aging on living carbon emissions, which are initially inhibited and then promoted, with different “turning points” for rural and urban regions. As income levels rise, population aging has a marginally increasing effect on living carbon emissions. However, upgrading the consumption expenditure structure, expanding family size, and increasing clean energy consumption can help mitigate the promoting effect of aging on emissions. The mediation model identifies four pathways through which population aging influences living carbon emissions, with income level and consumption expenditure structure playing key roles. This study offers policy insights for addressing urban‐rural disparities and fostering sustainable regional development.